Europeiska kommissionen och det diskursiva förhållningssättet till Gazakriget: En kritisk diskursanalys av det normativa språkbruket mellan 07.10.2023 - 11.03.2025 - Ågren,Matilda (2025)
On October 7, 2023, Hamas launched an attack in Israel, killing approximately 1,200 Israelis and taking hundreds hostage. In response, the Israeli government initiated a large-scale military operation in Gaza. As of March 2025, the strip is left in ruins with more than 50,000 Palestinians estimated to have been killed by Israeli warfare. The war has resulted in a fragmented and deeply divided international community. Amidst such a conflicted political reality, this thesis investigates the European Commission’s discursive articulations concerning the Gaza war between October 2023 and March 2025. Through a methodological application consisting of Norman Fairclough’s three-dimensional model of critical discourse analysis (CDA) complemented by Ian Manner’s concept of Normative Power Europe (NPE), the thesis examines the Commission’s discourse as well as how the institution constructs its normative identity in relation to the conflict. Particular analytical attention is given to the five core EU-norms theorized by Manners, namely human rights, rule of law, peace, liberty, and democracy. These norms guide the analysis and serve to refine the CDA. The empirical material consists of 31 statements, press releases, speeches, and articles, all published on the Commission’s official website relating to the situation in Gaza. The analysis finds that the Commission’s discourse includes articulated messages in line with its normative and value-driven identity. The Commission presents itself as an active and morally responsible global actor. However, tensions and paradoxes arise concerning the normative discourse, as the proclaimed normative values clash with a linguistic restraint and cautious approach towards Israel, even at such a critical juncture in the Israel-Palestine conflict.
Keywords: European Commission; Gaza war; Israel/Palestine; Normativity; Critical Discourse Analysis; European Studies